Towards the development of an integrated modelling framework underpinned by mineralogy - Ntlhabane, Sithembiso (Centre for Minerals Research, 2019)
The mining industry is under increased pressure from many stakeholders to be forward thinking in its approach to sustainability. This requires a holistic approach to address techno-economic, environment and social issues, rather than just focusing on individual aspects of sustainability practice. The ability to do so requires an integrated modelling framework, underpinned by mineralogy so that the effect of ore variability on one or more of these factors can be simultaneously evaluated and optimised. This study focuses on the steps towards the development of this proposed framework using a case study of a polymetallic sulfide ore flotation circuit. The initial focus in the framework development is on integrating the techno-economic and the environmental aspects of sustainability. Thereafter the framework is used to consider a variety of scenarios evaluating the balance between techno-economic value and environmental burden. A sampling exercise was conducted around the intermediate and terminal streams of the flotation circuit processing polymetallic sulfide ore. All samples were characterised using both chemical assays and mineralogy (QEMSCAN). This formed the input data for the development of an ore specific element to mineral conversion (EMC) recipe that converts chemical assays to mineral grades. The EMC technique has the advantage of being fast, inexpensive and can be used on a routine basis. The recipe for this specific polymetallic sulfide ore was designed to calculate nine minerals in four different rounds, using least square method in the first two rounds and non-negative least square in the last two rounds. Sulfide minerals (chalcopyrite, galena and sphalerite) were calculated in the first round, barite was estimated in the second round, silicate minerals (garnet, biotite and quartz) were determined in the third round and pyrrhotite and magnetite were calculated on the last round. Data validation for EMC was performed by comparing calculated mineral grades against the measured mineral grades obtained from QEMSCAN. The accuracy was determined by evaluating the R2 value, the results were comparable as the R2 value was above 0.95 for all minerals. Mineral grades obtained from EMC of the assayed streams were used to carry out a mineral mass balanced of the flotation circuit. From the results, mineral grade and recovery were calculated and were used to evaluate metallurgical performance across the flotation circuit. The chalcopyrite (copper) concentrate was diluted with pyrrhotite (26 wt. %). The sphalerite concentrate (zinc) had the highest grade (94 wt. %) followed by galena (lead) with a concentrate grade of 85 wt. %. Sphalerite and galena achieved high recoveries over 90 %. From analysis of the flotation performance of the circuit, the results demonstrate an opportunity to improve the copper (chalcopyrite) concentrate quality. The diluted concentrate is likely to attract penalties during downstream processing (e.g. smelter) due to the presence of impurities (pyrrhotite). The concentrate can be upgraded by rejecting pyrrhotite in the first stage of the copper circuit. In addition, the mass balanced mineralogy results were used to calculate a theoretical potential of the final tailings to generate acid rock drainage (ARD). The ARD method used is based on the relative abundance of acid generating sulfide minerals (chalcopyrite, galena, sphalerite and pyrrhotite) and other minerals with the theoretical potential to neutralise the acid generated. The net mineralogically calculated acid producing potential was estimated as 46.4 kg H₂SO₄/ton. To further demonstrate the usefulness of the framework, a mineral splitter function was used to model the flotation circuit and test different hypothetical scenarios. Two hypothetical scenarios were investigated relative to the current operating condition of the flotation circuit. A sensitivity analysis on both scenarios was conducted to assess the effect of feed ore variability. The pyrrhotite feed grade was varied between 10 and 100 % of the base case and all sulfide mineral recoveries were kept constant. Scenario I considered improving Cu (chalcopyrite) concentrate grade in the Cu circuit by rejecting pyrrhotite. A Monte Carlo simulation was carried out by varying the pyrrhotite recovery to concentrate from a minimum of 2 % to a maximum of 18 % in the mineral splitter function. The results showed an increase in pyrrhotite grade in the final zinc tailings and an increase in the mineralogically calculated ARD potential (up to 53.9 kg H₂SO₄/t for tailings). Scenario II considered the installation of a magnetic separator to concentrate pyrrhotite in the final tailings and achieved a net acid producing potential of 15.2 kg H₂SO₄/t, which was lower than scenario I. The sensitivity analysis of scenario I showed a correlation between increased pyrrhotite feed grade with mineralogically calculated ARD potential (89.6 kg H₂SO₄/t). The results from sensitivity analysis of scenario II were lower were than scenario I (28.6 kg H₂SO₄/t). This shows that installation of a magnetic separator has the potential to mitigate ARD formation and produce a potential economic magnetite concentrate by-product. In conclusion this study has shown how mineralogy can be integral in developing an integrated modelling framework for simultaneously assessing techno-economic and environmental performance. The developed framework demonstrated the possibility of simultaneously balancing the trade-off, improving grade and mitigating the risk of ARD formation. It is a conceptual starting point for a new approach to traditional process mineralogy studies to start implementing sustainable development aspects on the operational level.